Two new Patagonian species of Atrichopogon (Meloehelea) (Diptera: Ceratopogonidae) - Marino, Pablo Ignacio (2011)
Two new species of the subgenus Atrichopogon (Meloehelea) from Patagonia, Atrichopogon (M.)macrodentatum from the Nothofagus forests, and A. (M.) monomorphicus from steppe areas in the ecotone with forests, are described and a key of the Patagonian species of the subgenus is provided.